Measuring the Height of Clouds (Global Journal of Science Frontier Research, 2016)
Introduction-The International Atlas of Clouds was produced as a result of long observations and it lists 10 cloud species, 14 cloud types, 9 cloud subtypes, 9 accessory clouds and their possible varieties. The Cloud Atlas contains the characteristic features of clouds, their height measured from the Earth's surface, among others. The measured altitude values result from a great many instrumental measurements, so for the purposes of describing the height of a selected cloud species, the tables -due to the alterations of the volumes determining the atmosphere -contain not only one specific altitude value, but a series of values covering a wide range.
Keywords: Atlas of Clouds; wide range; cloud types